Pelatihan hypnobreasfeeding pada tenaga kesehatan untuk meningkatkan produksi ASI pada ibu menyusui - Zuraidah, Zuraidah; Aprilyadi, Nadi; Soewito, Bambang; Juartika, Wella (Nur Science Institute, 2024)
Breast milk is the best food for babies because it contains nutrients that best suit the needs of babies in the accelerated stage of growth and development, especially in the first 2 years. The service activity aims to increase the knowledge and skills of Health Workers, especially Midwives, in implementing hypnobreasfeeding for breastfeeding mothers in their work area. The hope is that the amount of breast milk will increase from the application of hypnobreasfeeding by midwives to mothers who breastfeed exclusively. The approach to community service activities uses socialization methods and hypnobreastfeeding training for 20 health workers, especially midwives. The results of the activity showed that there was an increase in the knowledge of Health workers. In the pretest, the officers' knowledge was in the sufficient category of 80 percent and 20 percent good, while in the posttest, it was in the good category of 100 percent. Based on these results, Hypnobreastfeeding training can effectively increase breast milk production in breastfeeding mothers. These results imply that health service providers can utilize the hypnosis techniques learned in training to provide more effective assistance to breastfeeding mothers.